2017
DOI: 10.5897/ajfs2016.1550
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of ready-to-eat meats vended in highway markets in Uganda

Abstract: Ready-to-eat (RTE) meats are products sold to consumers which do not require significant further processing except re-heating or completion of cooking process. These meats may constitute a likely potential hazard to human health due to non-compliance with food safety regulations by food handlers. This study was aimed at evaluating the bacteriological safety of RTE roasted meats sold by selected food vendors in Lukaya and Najembe highway markets. Bacteriological analyses were conducted on 20 samples for each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
5
4
1
Order By: Relevance
“…The first rainy season in Uganda is normally wetter than the second season (Nsubuga et al, 2014), which may account for the different results in the two seasons. This finding partly corroborates the report by Bagumire and Karumuna (2017) that microbial loads in ready-to-eat meat sold along high ways in Uganda during the wet season were higher than in the dry season. The specific reasons for the higher bacterial counts in R. differens samples from Masaka than those from Kampala in the first season remain unknown.…”
Section: Discussionsupporting
confidence: 91%
“…The first rainy season in Uganda is normally wetter than the second season (Nsubuga et al, 2014), which may account for the different results in the two seasons. This finding partly corroborates the report by Bagumire and Karumuna (2017) that microbial loads in ready-to-eat meat sold along high ways in Uganda during the wet season were higher than in the dry season. The specific reasons for the higher bacterial counts in R. differens samples from Masaka than those from Kampala in the first season remain unknown.…”
Section: Discussionsupporting
confidence: 91%
“…Mass isolation of coliform bacterial in roasted fish could be due to the high presence of water activity (fluid) contained in the fish product compare to that of doughnuts, suya and meat pie with low water activities or post-harvest contamination through food handlers and the environment which was above the standards for ready-to-eat-foods recommended by ICMSF (1996). The findings in this study is in agreement with the work of Ananias and Rowland (2017) who reported that chicken products were more vulnerable to contamination because chicken contains more fluid than beef and goat meat which could facilitate quick multiplication of coliforms. The issue of fish handling during processing, type of water used in cleaning the fish, the environment of operation where the cleaning, processing, preservation and storage coupled with display may account for high coliform load.…”
Section: Microbial Quality Of Street Vended Foods (Svf) During Rainy ...supporting
confidence: 93%
“…The presence of dusty environment and other human activities might have supported the growth rate of TCC. The isolation of coliform presumes the identification of potential disease-causing bacteria and thus the presence of coliform is a signal for the determination of microbial pollutant in SVF which is in agreement with the work of Ananias and Rowland (2017).…”
Section: Microbial Quality Of Street Vended Foods During Dry Seasonsupporting
confidence: 81%
“…In this study, four different bacteria were isolated and identified which are Staphylococcus aureus, Salmonella spp, Shigella spp and Escherichia coli and similar findings of some of these bacteria have been earlier reported by several workers [21][22][23][24][25][26][27][28][29][30][31]. Bacteria such as Staphylococcus aureus, Escherichia coli, Salmonella spp, and Shigella spp observed in this study are of public health importance as they have been found to be related to various diseases of man such as gastroenteritis.…”
Section: Discussionsupporting
confidence: 73%
“…[28] Ananias et al [30] and Falegan et al [31] who also recorded Staphylococcus aureus as the most frequently isolated bacteria and highest percentage occurrence. However, this result is in disagreement with the findings of Moshood et al [8]; Manyi et al [39] and Samuel et al [26] and Uze et al [25] who identified Bacillus cereus, Escherichia coli, Bacillus subtilis, Salmonella species, and Bacillus subtilis and Enterobacter aerogenes respectively, as the most frequently isolated bacteria.…”
Section: Discussionmentioning
confidence: 99%